The Coldest Winter I Ever Spent - Jacobus, Ann (Minneapolis, MN : Carolrhoda Lab, 2023)
Eighteen-year-old Del is in a healthier place more than a year after a suicide attempt, but her aunt's terminal cancer diagnosis forces her to confront the demons she has been keeping at bay.
new ya book 2023 summer.
Ages 13-18.
Grades 10-12.
Keywords: Emotional problems -- Fiction; Right to die -- Fiction; Terminally ill -- Fiction; Fiction; Novels